Some Comments on the Nonlinear Dynamics of a Portal Frame under Base Excitation - Aline Souza de Paula; José Manoel Balthazar; Jorge Luis Palacios Felix (Shock and Vibration)
This paper presents a nonlinear dynamic analysis of a flexible portal frame subjected to support excitation, which is provided by an electro-dynamical shaker. The main goal of this study is to investigate the dynamic interactions between a flexible portal frame and a nonlinear electrical support excitation. The numerical analysis shows a complex behavior of the system, which can be observed by phase spaces, Poincaré sections and bifurcation diagrams.